Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1101/2023.01.18.23284589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harnessing Transcriptomic Signals for Amyotrophic Lateral Sclerosis to Identify Novel Drugs and Enhance Risk Prediction

Abstract: Introduction: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease. This study integrates the latest ALS genome-wide association study (GWAS) summary statistics with functional genomic annotations with the aim of providing mechanistic insights into ALS risk loci, inferring drug repurposing opportunities, and enhancing prediction of ALS risk and clinical characteristics. Methods: Genes associated with ALS were identified using GWAS summary statistic methodology including SuSiE SNP-based fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, they alone are not sufficient for translation into clinical practice. Future studies should aim to extend any associations found by integrating functional and multi-omics datasets to gain mechanistic insights into observed trends and facilitate treatment discovery 62,67 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they alone are not sufficient for translation into clinical practice. Future studies should aim to extend any associations found by integrating functional and multi-omics datasets to gain mechanistic insights into observed trends and facilitate treatment discovery 62,67 .…”
Section: Discussionmentioning
confidence: 99%
“…However, they alone are not sufficient for translation into clinical practice. Future studies should aim to extend any associations found by integrating functional and multi-omics datasets to gain mechanistic insights into observed trends and facilitate treatment discovery 58,63 . The fine-mapping and colocalisation analysis pipeline we have used is available as an openaccess resource on GitHub to facilitate the application of these methods in future studies: https://github.com/ThomasPSpargo/COLOC-reporter.…”
Section: Targeted Genetic Analysesmentioning
confidence: 99%
“…Furthermore, it allows exploration of expression-related genetic mechanisms underlying the GWAS association signals already identified (PRNP, STX6, GAL3ST1) uncovering further mechanistic insights into sCJD risk loci, in addition to nominating new TWAS/PWAS significant prioritized risk genes within subthreshold loci for generating novel disease-relevant hypotheses. Importantly, there are precedents of similarly designed studies achieving these goals in other neurological diseases [12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%